2015
DOI: 10.1080/17441692.2015.1117119
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic disparities in household secondhand smoke exposure among non-smoking adolescents in the Republic of Korea

Abstract: This nationally representative study examined (a) gender and age differences in household secondhand smoke exposure (HSHSE) and (b) associations between socioeconomic status (SES) and HSHSE among non-smoking Korean adolescents. Two subsamples were analysed: males (n = 25,648) and females (n = 30,240). The HSHSE measures were incidence of HSHSE (yes/no) and number of days of HSHSE (1-7 days); the SES measures were parental education, perceived economic status, and family wealth. For the first aim, chi-square te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 62 publications
1
11
0
1
Order By: Relevance
“…42,43 Fourth, SHS is a risk factor for inflammation and the production of inflammatory cytokines, which can indirectly increase risk for depression and depressive symptoms. 44,45 Finally, although the regression models were adjusted for food insecurity (a proxy of SES), it is possible that adolescents exposed to SHS are more likely to live in disadvantaged neighborhoods than those not exposed to SHS, 46 and this could also partly explain the findings. If corroborated by further longitudinal studies, these findings suggest that reducing SHS exposure may be important not only for the prevention of physical diseases such as ischemic heart disease, lung cancer, and asthma, 47 but also for adolescent depressive symptoms in LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 Fourth, SHS is a risk factor for inflammation and the production of inflammatory cytokines, which can indirectly increase risk for depression and depressive symptoms. 44,45 Finally, although the regression models were adjusted for food insecurity (a proxy of SES), it is possible that adolescents exposed to SHS are more likely to live in disadvantaged neighborhoods than those not exposed to SHS, 46 and this could also partly explain the findings. If corroborated by further longitudinal studies, these findings suggest that reducing SHS exposure may be important not only for the prevention of physical diseases such as ischemic heart disease, lung cancer, and asthma, 47 but also for adolescent depressive symptoms in LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also highlighted the higher likelihoods of ETS exposure at home for socioeconomically-disadvantaged people [46,47,48,49]. The present study has documented that, even though the smoking prevalence among social aid recipients tends to be higher [43], the prevalence of ETS exposure for the population of the Piotrkowski District was found to be much lower than in the general population, where 15.5% of the non-smokers (6.6% of males and 18.3% of females, respectively) were exposed to ETS in the month preceding the study.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] A recent Korean study using data from another survey also confirmed that lower SES was associated with higher odds of household secondhand smoke exposure in Korean adolescents. 34 Increased parental enthusiasm for children's education in high SES populations could affect the myopic development. Therefore, confounding effects of parental SES on passive smoking may underlie in the inverse association between urinary cotinine concentration and myopia.…”
Section: Discussionmentioning
confidence: 99%